Monitoring and Analysis Solid Formulation Dissolution Phenomenon with Image Recognition Technologies. (14th September 2022) - Wang, Haoyu; Kwong, Chiew Foong; Liu, Qianyu; Liu, Junyao; Liu, Zhixin; Lee, Boon Giin; Huang, Liang
Abstract : The dissolution test has become the most important quality index in the research and development of solid formulation, especially the evaluation of drug bioequivalence. However, it had low operability, was tedious, and was always overlooked. The previously related studies required a fixed tablet and analysed the recorded video by disso GUARO PRO and Microsoft Paint™. Therefore, we have developed a novel image recognition system to automatically track the moving tablet and analyse the volume change at the same time. Image recognition technology is often used to monitor the dissolution process. The camera system with visible light and infrared camera functions was placed on the dissolution tester. The system collects the plate image for binary processing and then records and calculates its pixel area, which can automatically record the volume change of the tablet in the dissolution test, no matter disintegration or corrosion.